2016
DOI: 10.5539/ijc.v8n2p123
|View full text |Cite
|
Sign up to set email alerts
|

Content of sP-selectin and Cytokines in Blood of Patients with Type 2 Diabetes Mellitus and Arterial Hypertension Depending on Diabetes Compensation Condition

Abstract: The goal of our research has been to study sР-selectin and cytokine content changes, namely ІL-2, ІL-6 and TNF-α in blood plasma of patients with type 2 diabetes mellitus with varying compensation for the disease and arterial hypertension, as well as to investigate a possible interrelation between sР-selectin and cytokines. To achieve the goal 137 patients with type 2 diabetes mellitus with AH of the І-ІІ stages and without AH (72 women and 65 men) have been examined. The levels of sР-selectin, ІL-2, ІL-6, TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Similarly, Hameed et al (28) found that no significant difference between sP-selectin and age, gender, smoking, arterial hypertension and hyperlipidaemia. However in other study they found that the level of sP-selectin in blood increases with deterioration of type 2 diabetes mellitus compensation and arterial Hypertension (29) . In our study patient diabetic and hypertension patient were excluded.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, Hameed et al (28) found that no significant difference between sP-selectin and age, gender, smoking, arterial hypertension and hyperlipidaemia. However in other study they found that the level of sP-selectin in blood increases with deterioration of type 2 diabetes mellitus compensation and arterial Hypertension (29) . In our study patient diabetic and hypertension patient were excluded.…”
Section: Discussionmentioning
confidence: 83%
“…В ряде работ показано, что провоспалительные цитокины, в том числе и интерлейкин 1 (IL1), цитотоксичны для β-клеток, они участвуют в развитии эндотелиальной дисфункции, IL1 в организме запускает локальную воспалительную реакцию в ткани поджелудочной железы, а также каскад продукции других цитокинов, что в конечном счёте приводит к активации Т-и В-лимфоцитов. «Хроническая» секреция IL1 приводит к модификации Т-хелперов, которые в свою очередь активируют цито-токсические T-лимфоциты, воздействие которых приводит к необратимому разрушению β-клеток поджелудочной железы [2][3][4][5]. Прямым антагонистом IL1 c противовоспалительными свойствами и со способностью ингибировать производство воспалительных цитокинов и хемокинов является IL10, кодируемый одноимённым геном.…”
Section: Introductionunclassified